Glucose control in Rwandan youth with type 1 diabetes following establishment of systematic, HbA1c based, care and education. Issue 1 (January 2015) - Marshall, Sara L.; Edidin, Deborah V.; Arena, Vincent C.; Becker, Dorothy J.; Bunker, Clareann H.; Gishoma, Crispin; Gishoma, Francois; LaPorte, Ronald E.; Kaberuka, Vedaste; Ogle, Graham; Sibomana, Laurien; Orchard, Trevor J.
Highlights We assessed improvement in glycemic control in Rwanda youth with diabetes. 2 yr after introduction of education and A1c testing mean A1c fell from 11.2 to 9.8%. Hypertension was very common affecting over 40% of the population during follow up. Different patterns of glycemic control over time were noted. Those with worst control measured their glucose less frequently.